Why does job insecurity influence employees proactivity differently? A dual-path model based on dualistic passion - Zhu, Mingming; He, Kaiyuan; Qiang, Ziyang (Frontiers in Psychology, 2025)
IntroductionJob insecurity (JI) has become a salient feature of contemporary work environments and a challenge that employees must address. However, scholars hold competing perspectives on the reasons why employees adopt different coping strategies in response to JI. To address this paradox, this study draws on Conservation of Resources (COR) theory and the Dualistic Model of Passion, to develop and test a dual-path model that explains how and why employees proactively respond to JI.MethodsWe conducted a two-wave survey of 384 employees from China, examined the mediating roles of obsessive and harmonious passion and the moderating role of performance climate.ResultsThe results show that: (1) JI is only marginally and negatively associated with task proactivity; (2) JI positively predicts task proactivity through obsessive passion while negatively predicting it through harmonious passion; (3) Performance climate strengthens the positive indirect effect of JI on task proactivity via obsessive passion.DiscussionThese findings clarify the competing mechanisms between JI and task proactivity, and extend COR theory by specifying the conditions under which resource investment occurs. This study provides practical guidance for organizations seeking to encourage employees to adopt adaptive responses while safeguarding employees’ sustainable engagement.